Endocrine Disruptors - Ayşegül AKSAN; Aslıhan ÖZDEMİR (Hacettepe University, 2016)
Endocrine disruptors are exogenous substances or mixtures that alter function(s) of the endocrine system and consequently cause adverse health effects in an intact organism, or its progeny, or (sub)populations. These substances may alter the production, release, transport, metabolism, binding, action, elimination and even their effects on target cells. Endocrine disruptors usually present their functions through steroidal or peptide/protein hormones. Gene metilations as a result of exposure endocrine disruptors in early stages life cause the basis of developing adult diseases and these genetic changes pass down from generation to generation. In this review; definition, classification, physiologic actions of endocrine disruptors are revealed with information on health, and also the interaction relation between endocrine disruptors and reproductive health, thyroid functions, obesity, diabetes mellitus, metabolic syndrome and nutrition as are discussed.